2017
DOI: 10.1128/mbio.00537-17
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Paracoccin Gene Silencing on Paracoccidioides brasiliensis Virulence

Abstract: Among the endemic deep mycoses in Latin America, paracoccidioidomycosis (PCM), caused by thermodimorphic fungi of the Paracoccidioides genus, is a major cause of morbidity. Disease development and its manifestations are associated with both host and fungal factors. Concerning the latter, several recent studies have employed the methodology of gene modulation in P. brasiliensis using antisense RNA (AsRNA) and Agrobacterium tumefaciens-mediated transformation (ATMT) to identify proteins that influence fungus vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(42 citation statements)
references
References 45 publications
2
40
0
Order By: Relevance
“…Concerning the mice survival to the fungal infection, we observed that all animals infected with wt-PCN yeasts survived throughout a 40 days post-infection period, whereas the ones infected with ov-PCN yeasts started dying at day 27 post-infection and none survived to a 35 days post-infection period (Fig 3F). We concluded that PCN overexpression aggravates the disease caused by P. brasiliensis yeasts, reinforcing the notion that PCN acts as a P. brasiliensis virulence factor [18].…”
Section: Resultssupporting
confidence: 75%
See 4 more Smart Citations
“…Concerning the mice survival to the fungal infection, we observed that all animals infected with wt-PCN yeasts survived throughout a 40 days post-infection period, whereas the ones infected with ov-PCN yeasts started dying at day 27 post-infection and none survived to a 35 days post-infection period (Fig 3F). We concluded that PCN overexpression aggravates the disease caused by P. brasiliensis yeasts, reinforcing the notion that PCN acts as a P. brasiliensis virulence factor [18].…”
Section: Resultssupporting
confidence: 75%
“…Recently, we have shown that PCN-silenced yeasts of P. brasiliensis are unable to perform the morphological transition from yeast to mycelium [18]. Herein, we studied the transition of ov-PCN yeasts by quantitative optical microscopy, for 7 days (168 h) following the shift in culture temperature from 37 to 25 °C.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations